2019
DOI: 10.1108/oir-09-2016-0286
|View full text |Cite
|
Sign up to set email alerts
|

Building online citizen engagement for enhancing emergency management in local European government

Abstract: Purpose -The purpose of this paper is to examine European citizen engagement for enhancing emergency management and, more specifically, in the context of the terrorist attacks which occurred in Paris, France on November 15, 2015. To do so, two main research questions are raised. First, are there differences in the levels of citizen engagement between the country affected, France, and other European countries? Second, what factors foster a high level of citizen engagement in France? Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
(75 reference statements)
1
24
0
1
Order By: Relevance
“…Most studies have evaluated engagement using quantitative indicators of social media platforms, like the number of repost, comments, and likes [ 94 , 95 , 96 ] (Bonson and Ratkai, 2013; Agostino and Arnaboldi, 2016; del Mar Galvez Rodriguez et al, 2019). These three indicators respectively reflect the engagement behavior of the users.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have evaluated engagement using quantitative indicators of social media platforms, like the number of repost, comments, and likes [ 94 , 95 , 96 ] (Bonson and Ratkai, 2013; Agostino and Arnaboldi, 2016; del Mar Galvez Rodriguez et al, 2019). These three indicators respectively reflect the engagement behavior of the users.…”
Section: Methodsmentioning
confidence: 99%
“…Literature has shown that public engagement is paramount in crisis management, as it improves the community's capacity to get through the different stages of an emergency effectively (G alvez-Rodr ıguez et al, 2019). Specifically, during an epidemic, the nonpharmaceutical interventions' success to slow or hinder the spread of a virus relies heavily on citizens' compliance and co-operation (French, 2011;Han et al, 2020).…”
Section: Aaaj 351mentioning
confidence: 99%
“…Social media, such as Facebook, Twitter, and Weibo, offers an effective channel for the public to engage with information dissemination during major emergencies, such as health crises and natural disasters [ 15 , 63 , 64 ]. Through social media, the public can understand the current situation about an emergency [ 69 , 74 ], and governments or organizations can also improve their capabilities in processing emergency information and providing better public social services [ 14 , 15 , 24 , 77 ]. Due to the openness and participatory nature of social media, it offers vital benefits in information dissemination between citizens during emergencies and brings new ways to engage citizens with emergency management [ 4 ].…”
Section: Introductionmentioning
confidence: 99%